Can Top Down Participatory Budgeting Work? The Case of Polish Community Fund - Dawid Sześciło; Bartosz Wilk (Central European Public Administration Review)
The article addresses the participatory budgeting (PB), which is one of the most recognised governance innovations of recent decades. This global phenomenon represents in practice a shift towards participatory and collaborative management of public resources at the local level. The purpose of this article is to determine when top down approach to PB might be welcomed, taking into account the characteristics of PB schemes all around the world that they emerged as local initiatives, instigated either by civil society groups or local governments. The analysis is based on the description of the PB example as introduced via country-wide legislation, exhaustively regulating PB procedure. The article examines Polish experience in the field of functioning top down approach to PB. It demonstrates that top down PB can effectively work, if it is accompanied with significant incentives and grants, as well as the extensive autonomy and flexibility of local communities. Polish experience suggests that such an initiative might be relatively successful, yet there is a number of conditions that has to be met in order to ensure the dissemination of legislative model of participatory budgeting. The results have practical implications to central government institutions that consider introduction of some legislative framework for participatory budgeting at the local level. The originality of the research is in the analysis of one of successful stories of the PB introduced via country-wide legislation, and determining when this approach can work, also in other countries.